A STUDY ON INTERSTATE FREIGHT MODE CHOICE BETWEEN TRUCKS AND TRAINS USED TO TRANSPORT OIL PRODUCTS: A CASE STUDY OF IRAQ - Hussein M. NOOR; Noor M. ASMAEL (Transport Problems)
Freight mode choice is an important stage in shipping demand modeling. Transporting oil products using trucks between cities has several issues, including increased risk of accidents, higher transportation costs, environmental impact, and traffic congestion. Due to the absence of local studies, in addition to the few global studies that deal with freight mode selection used to transport oil derivatives between cities, the aim of the study is to develop transport mode choice models for trucks and trains transporting oil products between the interstate capital of Baghdad and the government of Basra for export. The revealed preference survey was used for 277 goods transport data collected with the help of personal interviews, questionnaires, and government institutions. The collected data were processed using two statistical approaches: binary logistic regression and Firth logistic regression. The study’s findings assist decision-makers in selecting sustainable modes of transport.